APPLICATION OF THE WEIGHT PRODUCT METHOD FOR PRIORITIZING CONSTRUCTION PROJECTS - Denny Jean Cross Sihombing (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
As a dynamic and complex sector, the construction industry is often faced with challenges in managing projects and determining their priorities. In the context of intense business competition and changes in the external environment, this research highlights the importance of developing efficient methods for prioritizing construction projects. The focus is on applying the Weight Product (WP) method, a decision-making framework, to score projects based on cost, time, quality, and risk criteria. The method integrates data collection, analysis, modeling, and ranking. The results identify projects that align with the company's priority objectives, while the systematic steps can provide practical guidance for construction companies in optimizing resource allocation. This research also has the potential to contribute to the literature and practice of the construction industry, as well as be the basis for developing more advanced applications and decision-making methods and priority project selection applications